PENGEMBANGAN ASESMEN METAKOGNISI CALON GURU IPA MELALUI PEMBELAJARAN BERBASIS MASALAH - Anggun Zuhaida (JURNAL PENELITIAN, 2015)
This research aims to develop a metacognition assessment for students of IPA teacher candidates through problem-based learning. Subjects tested in this study were 30 students in the Department Tadris IPA IAIN Salatiga using one group pretest-posttest design. Assessment isdeveloped based on metacognition indicators including an essay test assessment, performance assessment, assessment of attitudes and self assessment. The result of essay test indicates an increase in the ability of metacognition in general by the N-gain of 0.5 (medium category) where as performances and attitudes assessment lie in the good and excellent categories, while the self-assessment shows improvement results with N-gain of 0:45 (medium category). Overall, problem-based learning enhances the skills of metacognition that is "evaluation" on students of IPA teacher candidates.